Reinforcing Column Enlargement Using the Chemical Anchor Method in a Hotel Construction Project - Ety Fitriyani; Hulfa Istikomah; Vivid Lucha Deanggi; Saddam Mirza; Demmy Adhi Mulya Darma; Mutia Gina Savira (G-Tech: Jurnal Teknologi Terapan, 2026)
This study aims to identify the need for reinforcing column enlargement of a coffee shop structure in a hotel project due to concerns related to the adequacy of the existing column capacity during the construction stage. The evaluation was conducted through a three-dimensional structural reanalysis using SAP2000, based on the design drawings, material quality, and load combinations as specified in the project standards. The results of the analysis showed that most of the existing K1 columns, measuring 150 x 1000 mm, had a stress ratio exceeding 1.0, with the highest value reaching 1.32. It means that they do not meet the strength criteria and need reinforcement. The selected alternative was to enlarge the column dimensions to 250 x 1000 mm by adding 14D19 reinforcement and applying the chemical anchor method to ensure monolithic action between the old and new concrete. The reanalysis reduced the maximum stress ratio of the reinforced columns to 0.85, so that all columns satisfied the strength criteria. Verification of the chemical anchor system showed that all failure modes had load-to-capacity ratios below 1.0, with a maximum of 0.56 in the pull-out/bond mode. In terms of quality, time, and cost, the chemical anchor method was more efficient than the steel jacketing composite method, with an estimated 30–40% reduction in execution time and approximately 25% lower cost.